The effect of the source and the concentration of polymers on the release of chlorhexidine from mucoadhesive buccal tablets - Al-Ani, Enas (Saudi Pharm J, 2019)
In the current work, two groups of chlorhexidine mucoadhesive buccal tablets were prepared, using either rod or irregularly-shaped spherical particles of hydroxypropyl methylcellulose and different ratios of poloxamer 407 (P407). The tablets were designed to release the drug over two hours. Their physicochemical properties and drug release profiles were investigated. The impact on dry granulation, the ex-vivo mucoadhesion, the swelling index, the morphology of swollen tablets and the drug release kinetic were investigated. Drug-polymers chemical interaction was studied using Fourier Transforms Infrared Spectroscopy (FTIR) and differential scanning calorimetry (DSC). Due to different particle shapes, the preparation of dry granules required a 40 KN force for rod-shaped particles compared to 10 KN for the irregularly-shaped spherical particles. All formulations showed at least two-hours residence time using ex-vivo mucoadhesion. Statistically, there was no significant difference in the swelling index, drug release nor its kinetic for both groups. However, the microscopical morphology of the swollen tablet and the size of the pores were affected by particle shape. Increasing the ratio of P407 to 62.5% resulted in a pronounced increase in drug release from around 60% to >90% after two hours. Following the FTIR and DSC analyses, no chemical interaction was noted apart from the steric hindrance effect of P407, which was observed even with the physical mixtures.